2020
DOI: 10.1093/mnras/staa2518
|View full text |Cite
|
Sign up to set email alerts
|

Recovering variable stars in large surveys: EAup Algol-type class in the Catalina Survey

Abstract: The discovery and characterization of Algol eclipsing binaries (EAs) provide an opportunity to contribute for a better picture of the structure and evolution of low-mass stars. However, the cadence of most current photometric surveys hinders the detection of EAs since the separation between observations is usually larger than the eclipse(s) duration and hence few measurements are found at the eclipses. Even when those objects are detected as variable, their periods can be missed if an appropriate oversampling … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…Note the amplitude of variability of this RR Lyrae exhibited in the UVW2 filter is at least 1.5 magnitudes, while the ASAS-SN lightcurve 38 shows a V-band amplitude of only 0.4 magnitudes. Carmo et al 2020 for a review of these systems and example lightcurves; the inferred Gaia temperature is also consistent with this being an EA system).…”
Section: Variable Starssupporting
confidence: 62%
“…Note the amplitude of variability of this RR Lyrae exhibited in the UVW2 filter is at least 1.5 magnitudes, while the ASAS-SN lightcurve 38 shows a V-band amplitude of only 0.4 magnitudes. Carmo et al 2020 for a review of these systems and example lightcurves; the inferred Gaia temperature is also consistent with this being an EA system).…”
Section: Variable Starssupporting
confidence: 62%
“…It may be also important to investigate the possible effects that the adopted sample selection or methodology may have on the obtained results. Interestingly, a recent search for DEBs in CSS database by Carmo et al (2020) shows no significant inflation among selected targets. We understand the difficulties on deriving stellar physical parameters without spectroscopic data and on developing a model-independent analysis based only on photometry.…”
Section: The Mass-radius Diagrammentioning
confidence: 96%
“…Papageorgiou et al (2018) reported an updated catalog of 4683 eclipsing Algol-type binaries (EA) from the CSS survey. The physical parameters of the EA systems were explored by Lee (2015), Papageorgiou et al (2019a), andCarmo et al (2020). Using the same sample of 4683 EA in CSS, Papageorgiou et al (2021) reported 126 EAs with possible quadratic or cyclic period variations.…”
Section: The Catalina Samplementioning
confidence: 99%